Positive Psychological Capital as a Predictor of Satisfaction With the Fly-In Fly-Out Model - Soares Marques, Nazaré; Lopes, Miguel Pereira; Gonçalves, Sónia P. (Frontiers in Psychology, 2021)
The flexibility of the markets and international agreements lure a growing number of companies to expand their business beyond frontiers in search for new markets and a bigger business network. Workers, initially called expatriates, become keystones to implant and promote the so desired expansion into the international markets. From the concept of flexpatriate present in the literature in general, we adapted the concept of FLY-in FLY-out (FIFO) to comprehend the organizational flexpatriates. In the midst of the Positive Psychology theories, Luthans et al. underline that workers are the psychological capital of the companies. Therefore, the development of the Positive Psychological Capital becomes crucial and also contributes to the promotion of Job Satisfaction, nowadays a construct intertwined with well-being. The goal of our research is to test the PsyCap applicability to Portuguese flexpatriates of two different multinational companies. We developed and applied a micro-intervention based upon four constructs (hope, self-efficacy, resilience and optimism) following the suggestions of the Luthans et al. We aim to find if a bigger Positive Psychological Capital translates into a bigger Job Satisfaction of flexpatriates under the professional model FIFO. The research was conducted in three distinct moments, with the measurement of the levels of Positive Psychological Capital and Job Satisfaction before and after the micro-intervention and again three months later. The data collected shows indeed that the level of Positive Psychological Capital is connected with the level of Job Satisfaction and that this connection is positive: more Positive Psychological Capital, bigger Job Satisfaction. Furthermore, it shows that the micro-intervention enhances the Positive Psychological Capital and lasts in time (at least) three months